Pengukuran Status Gizi dan Pengobatan Penyakit Metabolik Warga Kelurahan Angke, Jakarta Barat - Yohana, Yohana; Meiyanti, Meiyanti; Kartadinata, Erlani; Margo, Eveline (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Pandemic Covid-19 had a serious impact on many aspects of living, which is health. Reducing the rate of transmission of Covid-19, the government issued regulations restricting the movement of people. Other health problems also arise along with increasing body weight, an unbalanced diet, and poor physical activity. Insufficient lifestyle could induce metabolic disease especially diabetes mellitus. In 2018, Riskesdas showed the prevalence of diabetes mellitus in Jakarta increased to 3.4%. One of the risk factors for diabetes mellitus is obesity. Obesity is characterized by increasing body weight as a result of an imbalance in energy consumption and energy expenditure. According to previous services, people who lived in the Angke area had lower income and education than others. This service aims to improve healthy lifestyles and health degrees during a pandemic. The method, which is used for instance examination, measurement of body mass index and giving treatment. The service was held on March 14, 2021, at the Pitakananda Buddhist temple in the Angke area, West Jakarta. Participants and the service team followed the health protocol as prevention transmission Covid-19. The results of the service showed certain participants classify with overweight around 50.9% and obesity over 21.1%. High blood pressure disease was found in about 19.3%. Participants who are investigated are provided with education, drugs, and supplements that could improve health status. The high enthusiasm of the participants encourages us to carry out regular service activities thus healthy eating habits and suitable physical activity could be established, health status could be improved.